2016
DOI: 10.1093/jpids/piw020
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 23 Gastrointestinal Pathogens Among Children Who Present With Diarrhea

Abstract: Toxigenic C difficile, diarrheagenic E coli, and norovirus were the leading organisms detected among these children with diarrhea. Viral pathogens are identified frequently among young children with acute gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
34
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 34 publications
10
34
1
4
Order By: Relevance
“…We then retrospectively analyzed downstream clinical management in these patients in comparison with a historical control population. We found that the GI panel had a high (32.8%) positivity rate which was similar to that of other published studies (5)(6)(7)(8). Piralla et al (9) tested 168 adult and pediatric patients with diarrhea and found an overall 54.8% positivity rate, with 28.3% having more than one organism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We then retrospectively analyzed downstream clinical management in these patients in comparison with a historical control population. We found that the GI panel had a high (32.8%) positivity rate which was similar to that of other published studies (5)(6)(7)(8). Piralla et al (9) tested 168 adult and pediatric patients with diarrhea and found an overall 54.8% positivity rate, with 28.3% having more than one organism.…”
Section: Discussionsupporting
confidence: 90%
“…One final possibility is that the Campylobacter, Shiga toxin, Cryptosporidium, and Giardia results identified by the GI panel were false positives, as they were not confirmed by conventional methods; however, this is unlikely, as these organisms fit well with the patients' clinical scenarios and the sensitivity of PCR is higher than that of culture, microscopy, or EIA (9). Stockmann et al (7) retrospectively performed the FilmArray GI panel on 378 diarrhea samples which had been collected for C. difficile and/or other stool pathogen testing. In 91 patients who had a sample submitted only for C. difficile testing, the GI panel identified Salmonella, Campylobacter, norovirus, astrovirus, sapovirus, and Giardia alone or in combination with C. difficile.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of single Adenovirus infection, only next to rotavirus, in our study tallies with the GEMS re-analysis study where, when assessed with PCR-based methods, Adenovirus incidence was five times more than previously reported using microbiological methods [17,22], shifting this enteropathogen to become among the top six diarrhoea attributable pathogens [23,24]. However, our study did not find attributable cases of moderate-to-severe diarrhoea due to Adenovirus.…”
Section: Discussionsupporting
confidence: 73%
“…This is of special relevance for children with co-infections, who represented a significant proportion of samples, mainly children !12 months of age. Rates of co-infection similar to those reported here have been described in other developing countries in studies using multiplex molecular diagnostic techniques (Duong et al, 2016), while studies performed using similar technology in more developed countries have described lower co-infection rates (Stockman et al, 2017). This contrast may be related to different sanitation systems and living standards.…”
Section: Discussionsupporting
confidence: 85%